Penerapan Pembelajaran Contextual Teaching and Learning (CTL) untuk Meningkatkan Pemahaman Konsep Siswa Tahfidz dan Reguler Materi Gerak Parabola (UPEJ Unnes Physics Education Journal, 2020)
This study aims to improve the understanding of the concepts of Tahfidz and regular students by applying Contextual Teaching and Learning (CTL) learning. The method used is a pre-experimental design in the form of a one-group pretest-posttest design. The population in this study was MIPA class X at MA Al-Asror Semarang in the 2018/2019 school year. The sampling used a purposive sampling technique and obtained Tahfidz students in class X MIPA 1 and regular students in class X MIPA 2, as an experimental class. Collecting data in this study using interviews, observation and test methods. The instruments in this study were interview sheets, observation sheets, and pretest-posttest questions. Based on the data analysis, the n-gain of class X MIPA 1 is 0.59 and n-gain of class X MIPA 2 is 0.67. Medium understanding of the concept of category. Contextual learning Teaching and Learning (CTL) can improve understanding of the physics concepts of parabolic motion material.